THE IMPACT OF AI ON LEARNING ENGLISH (International journal of artificial intelligence, 2026)
This study examines the impact of artificial intelligence on the process of learning English in modern educational contexts. The rapid development of AI technologies has significantly transformed traditional language teaching methods by introducing personalized, adaptive, and interactive learning environments. The paper analyzes how AI-based tools contribute to the development of key language skills, including pronunciation, vocabulary acquisition, grammar accuracy, writing proficiency, and communicative competence. Special attention is given to the role of AI in enhancing learner motivation, autonomy, and individualized learning pathways. In addition, the study discusses pedagogical challenges associated with the use of artificial intelligence, such as over-reliance on automated feedback, academic integrity concerns, and the need for effective teacher guidance. The findings suggest that when integrated thoughtfully and responsibly, artificial intelligence can substantially improve the effectiveness and accessibility of English language education.